2022
DOI: 10.5751/ace-02053-170113
|View full text |Cite
|
Sign up to set email alerts
|

Post-fledging survival, movements, and habitat associations of Gray Vireos in New Mexico

Abstract: Annual population growth in songbirds can be particularly sensitive to post-fledging survival, but research and management are frequently biased toward the nesting stage. Post-fledging information is particularly scarce for species breeding in desert bird communities, many of which have collapsed in recent decades. During 2017-2019 at Sevilleta National Wildlife Refuge, New Mexico, USA, we used radio telemetry to monitor survival, movements, and habitat associations of 90 fledgling Gray Vireos (Vireo vicinior)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…While some studies have also found that survival was not associated with specific vegetation characteristics (Hovick et al 2011, Fischer et al 2022, research in more complex habitats has shown that vegetation characteristics influence fledgling survival (King et al 2006, Moore et al 2010, Jenkins et al 2016. Research on another desert passerine, the Gray Vireo (Vireo vicinior), also found similar habitat associations for nesting and rearing fledglings, and no association between fledgling survival and measured habitat characteristics (Fischer et al 2022).…”
Section: Movement and Habitatmentioning
confidence: 99%
See 2 more Smart Citations
“…While some studies have also found that survival was not associated with specific vegetation characteristics (Hovick et al 2011, Fischer et al 2022, research in more complex habitats has shown that vegetation characteristics influence fledgling survival (King et al 2006, Moore et al 2010, Jenkins et al 2016. Research on another desert passerine, the Gray Vireo (Vireo vicinior), also found similar habitat associations for nesting and rearing fledglings, and no association between fledgling survival and measured habitat characteristics (Fischer et al 2022).…”
Section: Movement and Habitatmentioning
confidence: 99%
“…The median duration of passerine parental care has been reported to be 16 days for 126 north-temperate species (Russell 2000), and 77 species exhibit parental care for less than 20 days (Russell 2000). Bendire's Thrashers may benefit from prolonged parental care after fledging, which could lead to increased body mass, and reduced fledgling movements, and thus, higher recruitment (Tarwater and Brawn 2010, Vitz and Rodewald 2011, López-Idiáquez et al 2018, Fischer et al 2022.…”
Section: Movement and Habitatmentioning
confidence: 99%
See 1 more Smart Citation